Bafilomycin A1 inhibits SARS-CoV-2 infection in a human lung xenograft mouse model - Cuiling Zhang; Bingjie Wei; Zirui Liu; Wei Yao; Yiquan Li; Jing Lu; Chenchen Ge; Xiaoyang Yu; Dapeng Li; Yilong Zhu; Chao Shang; Ningyi Jin; et al. (Virology Journal, 2023)
Abstract Coronavirus disease 2019 is a global pandemic caused by SARS-CoV-2. The emergence of its variant strains has posed a considerable challenge to clinical treatment. Therefore, drugs capable of inhibiting SARS-CoV-2 infection, regardless of virus variations, are in urgently need. Our results showed that the endosomal acidification inhibitor, Bafilomycin A1 (Baf-A1), had an inhibitory effect on the viral RNA synthesis of SARS-CoV-2, and its Beta and Delta variants at the concentration of 500 nM. Moreover, the human lung xenograft mouse model was used to investigate the anti-SARS-CoV-2 effect of Baf-A1. It was found that Baf-A1 significantly inhibited SARS-CoV-2 replication in the human lung xenografts by in situ hybridization and RT-PCR assays. Histopathological examination showed that Baf-A1 alleviated SARS-CoV-2-induced diffuse inflammatory infiltration of granulocytes and macrophages and alveolar endothelial cell death in human lung xenografts. In addition, immunohistochemistry analysis indicated that Baf-A1 decreased inflammatory exudation and infiltration in SARS-CoV-2-infected human lung xenografts. Therefore, Baf-A1 may be a candidate drug for SARS-CoV-2 treatment.